Weldability and joining characteristics of AISI 420/AISI 1020 steels using friction welding - Kirik, I.; Ozdemir, N. (Carl Hanser Verlag, 2013)
The purpose of this study is to evaluate the welding characteristics of joints of martensitic stainless steel to medium carbon steel using friction welding. Martensitic stainless steel and commercial medium carbon steel each of 12 mm diameter were used to fabricate the joints. The friction welding tests were carried out using a direct-drive friction welding machine, which was designed and manufactured for this purpose by us. After friction welding, in order to determine the microstructural changes that occurred, the interface regions of the welded specimens were examined by means of scanning electron microscopy, X-ray diffraction and energy dispersive spectroscopy. Microhardness and tensile tests were conducted to determine the mechanical properties of the welded specimens. The experimental results indicated that martensitic stainless steel could be joined to AISI medium carbon steel using the friction welding technique and for achieving a weld with sufficient strength, the friction time has to be held as short as possible, while the rotational speed, friction and forging pressure have to be as high as possible.
Keywords: Friction welding; Martensitic stainless steel; Mechanical properties